Values and Character Education in the Context of National Education - Natalia, Devitri; Khatimah, Andi Weyana Nurul; Koli, Yulenni Bandora; Ilham, Ahmad; Agus, Andi Aco; Najamuddin, Najamuddin (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The problem of moral decline of the younger generation is currently increasingly concerning. Reality shows that many young generations have lost their national cultural identity, are involved in brawls, drugs, free sex, are involved in motorcycle gangs, bullying and the degradation of student morality which ultimately leads to juvenile delinquency. One effort to overcome this problem is to implement national values and character education in national education. This study aims to analyze the implementation of values and character education as an important foundation in the Indonesian national education system and to analyze the challenges in implementing national values and character education. Using a descriptive qualitative method through literature studies and research results show that values and character education in the context of national education is implemented through intracurricular, extracurricular, co-curricular learning, and habituation activities. The challenges in implementing values and character education are the lack of understanding and awareness among educators and parents, the inconsistency of the curriculum with the objectives of character education, dependence on academic assessments, limited human resources and infrastructure, negative influences from the social and technological environment, and the integration of character values that are less coherent.